2014
DOI: 10.1890/13-2309.1
|View full text |Cite
|
Sign up to set email alerts
|

Balancing anti‐herbivore benefits and anti‐pollinator costs of defensive mutualists

Abstract: Abstract. Quantifying costs and benefits of ostensibly mutualistic interactions is an important step toward understanding their evolutionary trajectories. In food-for-protection interactions between ants and extrafloral nectar (EFN)-bearing plants, tending by aggressive ants may deter herbivores, but it may also deter pollinators. The fitness costs of pollinator deterrence are not straightforward for long-lived iteroparous plants, because reproductive vital rates often contribute weakly to fitness relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 55 publications
3
58
2
Order By: Relevance
“…Our findings are inconsistent with some previous studies, in which the net effects of generalist predators on plant seed production are all positive (e.g., ants in Altshuler 1999; Ohm & Miller 2014;crab spiders in Louda 1982;Romero & Vasconcellos-Netor 2004;and Romero et al 2008). One possible explanation is that the intermediate herbivore species utilize different plant parts.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings are inconsistent with some previous studies, in which the net effects of generalist predators on plant seed production are all positive (e.g., ants in Altshuler 1999; Ohm & Miller 2014;crab spiders in Louda 1982;Romero & Vasconcellos-Netor 2004;and Romero et al 2008). One possible explanation is that the intermediate herbivore species utilize different plant parts.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar effects were also found in the flower-dwelling spider species Misumenops argenteus (Romero & Vasconcellos-Netor 2004). More recently, Ohm and Miller (2014) revealed that several ant species (Crematogaster opuntiae and Liometopum apiculatum) reduced pollinator visitation and seed production in the cholla cactus Opuntia imbricate, and this negative effect on plants could be balanced by the benefits of long-term protection from herbivores provided by the ants. Nevertheless, these studies focus exclusively on invertebrate predators, and the empirical evidence for the dual functional role of predators on plant fitness is still sparse for single predator species, and completely lacking for terrestrial vertebrate predators.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Helianthella quinquenervis occurs in wet and boggy montane meadows of Western North America (Weber 1952). Our data came from a population at Sevilleta National Wildlife Refuge in central New Mexico, USA (34°20′5.3″ N, 106°37′53.2″ W), where 1001 unique individuals were censused between 2004 and 2015 (see Miller et al [2009] and Ohm and Miller [2014] for details of study site and data collection). Opuntia imbricata is a cactus found throughout the deserts and arid grasslands of Southwestern North America (Benson 1982).…”
Section: Focal Species and Demographic Data Setsmentioning
confidence: 99%
“…Flower visits by this insect were significantly more frequent, and their duration significantly longer, on plants with ants present. This result was surprising, as aggressive ants have more often been seen to deter pollinators (Ness 2006;Assunção et al 2014;Ohm and Miller 2014), and pollinators have been observed to recognize the danger posed by ants (Hernández-Cumplido et al 2010;Assunção et al 2014). We are not alone, however, in observing increased pollination rates in the presence of ants.…”
Section: Discussionmentioning
confidence: 99%